The Effect of Using Gamma Rays on Morphological Characteristics of Ginger (Zingiber officinale) Plants - Kamaludin, Rashid; Abu Bakar, Mohd Daran; Arash, Nezhadahmadi; Khairul Hazmi, Zainoldin; Shamrulazhar, Shamzir Kamal; Shahril, Efzueni (Marsland Press / Zhengzhou University, 2013)
Ginger (Zingiber Officinale) was used to determine the effect of different exposure durations of Gamma ray on its growth. The exposure durations used were 30, 60, 90, 120 and 150 seconds. The research was carried out in the Greenhouse of Institute of Biological Sciences at the University of Malaya. The parameters used were germination rate, survival rate, and morphological studies (Seedlings height, the number of leaves, leaves length, leaves width and the number of roots). From the results, the average germination rate showed decrement with increment of Gamma ray exposure duration in which the average germination rate for the Control group was 43.68%, while for the Treatment group, the average germination rate was 40.35% for the Ginger with 30 seconds exposure duration, 32.75% for the Ginger with 60 seconds exposure duration, 25.70% for the Ginger with 90 seconds exposure duration, 25.92 % for the Ginger with 120 seconds exposure duration, and finally 24.48% for the Ginger with 150 seconds exposure duration. The survival rate also showed decrement with increment of exposure duration in which the survival rate for the Control plants was 95.24 %, but for Treatment ones, survival trate was 94.74% for the Ginger with 30 seconds exposure duration, 92.30% for the Ginger with 60 seconds exposure duration, 84.62% for the Ginger with 90 seconds exposure duration, 76.92% for the Ginger with 120 seconds exposure duration, and 75% for the Ginger with 150 seconds exposure duration. The growth of Ginger also showed decrement with increment of exposure duration. Gamma ray also caused some abnormalities in the Ginger. Some of the abnormalities were the formation of dwarf Ginger plants, Ginger plant with crooked stems and corrugated leaves. Generally, all the parameters showed decrement with increment of exposure duration of Gamma ray.